PENGEMBANGAN PENILAIAN PORTOFOLIO UNTUK MENDUKUNG KEAKTIFAN SISWA PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Shafirra Bulanrizkia Efanda; Laila Fatmawati (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
Learning will be memorable if students practice directly about the material being studied, but also the activity of students greatly affect their ability to absorb the material. With active students practice directly about the material being studied can help teachers in delivering the material being studied, especially on materials that are full of memorization as in the social studies in elementary school. For that new innovation is needed in the learning activities that are able to support students' activities in the learning process. This study aims to determine the steps of development of portfolio assessment and to determine the appropriateness of applying portfolio assessment to support student activeness in IPS learning. This research is a type of research development (R & D). The procedure is to conduct preliminary study to know the potential and problems, data collection, product design, design validation, design revision, product test, product trial revision. Portfolio assessment instruments are validated by expert testers, ie evaluation experts, materials experts and learning specialists. This research was conducted at SD Muhammadiyah Kalangan in May 2017. The data collection instrument was done with expert validation, observation sheet, and student response sheet. In this research, data analysis is done with qualitative and quantitative. The results showed that in terms of quality portfolio assessment included in the category of very good, which is suitable to be used as application of learning. The results obtained from the validation of the expert evaluation obtained a value of 68.75 with good category, the results of the material experts obtained a value of 77.78 with good category, and the results of the expert learning obtained a value of 100 with very good category. The result of the test based on the students' appraisal was obtained by 90.27 with very good category, from the observer scores obtained the value of 81.25 with very good category..